Antibodies Against G-Protein Coupled Receptors: Novel Uses in Screening and Drug Development - Gupta, Achla; Heimann, Andrea S.; Gomes, Ivone; Devi, Lakshmi A. (Combinatorial Chemistry & High Throughput Screening, 2008)
Antibodies are components of the body's humoral immune system that are generated in response to foreign pathogens. Modern biomedical research has employed these very specific and efficient molecules designed by nature in the diagnosis of diseases, localization of gene products as well as in the rapid screening of targets for drug discovery and testing. In addition, the introduction of antibodies with fluorescent or enzymatic tags has significantly contributed to advances in imaging and microarray technology, which are revolutionizing disease research and the search for effective therapeutics. More recently antibodies have been used in the isolation of dimeric G protein-coupled receptor (GPCR) complexes. In this review, we discuss antibodies as powerful research tools for studying GPCRs, and their potential to be developed as drugs themselves.